Upah Proses Dalam Pemutusan Hubungan Kerja - Gunadi, Fitriana (Jurnal Hukum & Pembangunan, 2020)
Wages is one of the elements in the employment relationship between an employer and a worker/employee based on the employment agreement. In accordance with the fundamental principle that is basically applicable to every workers/employees, wages will not be paid by employers if the workers/employees do not perform work (no work no pay). However in its development, there is an issue in the application of such principle since the ruling of the Decision of the Constitutional Court of Republic of Indonesia, which obliges employers to pay the wages to workers/employees who do not work because they are in the process of termination of employment until a decision has its permanent legal force (inkracht van gewijsde). The issue becomes even more complex when the obligation to pay wages is reaffirmed by the Supreme Court of Republic of Indonesia for 6 (six) months, thus the excess time in the industrial relations dispute process is not an obligation for employers.